Ignorance : literature and agnoiology - Bennett, Andrew, 1960 December 2- (Manchester University Press, 2009)
This text offers a new theory of & new ways of thinking about literature, with insights into literary theory. It offers an important rethinking of Romanticism & its influence on literary studies, from the 19th century to the present. It includes new readings of a range of authors including Wordsworth, Dickens & Seamus Heaney.